GAMBARAN POLA ASUH ORANG TUA YANG MEMILIKI ANAK AUTIS DI SLB NEGERI GEDANGAN - ., Erika Untari Dewi, Mira Ratna Sari (S1 Keperawatan, 2013)
Parenting is the attitude of parents interacting with their children. These include parental attitudes of parents in giving way rules, prizes and punishments, the way parents show their authority and how parents pay attention and respond to their children. Form pattern of authoritarian parenting include, permissive, and democratic. The research objective was to determine parenting parents who have children with autism in SLB NegeriGedangan. Design used in this study was descriptive with the single variable parenting parents picture. The population in this study were all parents who have children with autism in SLB NegeriGedangan. Sample in this study was similar to the total population because using sampling techniques, totaling 13 parents who have children with autism in SLB NegeriGedangan. Retrieval of data using questionnaires are processed in the form of frequency distribution table (percentage). Based on the results of the research overview parenting parents who have children with autism in the SLB Gedangan State (46.15%) by 6 respondents implementing parenting demokratif, (23.07%) 3 number of respondents implementing permissive parenting, (30.76% ) number 4 respondents applying authoritarian parenting. It is influenced by several factors including: age, education,occupation, number of children, never getting information and resources.Keywords: parenting, children with autism